Kemampuan Berpikir Kritis dan Penguasaan Konsep Dasar IPA Peserta Didik - Agus Ramdani; A Wahab Jufri; Jamaluddin Jamaluddin; Dadi Setiadi (Jurnal Penelitian Pendidikan IPA, 2020)
Students must be able to think at a high level in order to meet the requirements of the 21st century, including the ability to think critically. The mastery of student concepts about a material being studied influences the ability to think critically. The thing to remember is that all forms of critical thinking would not be possible without the main component of mastery of concepts. The purpose of this study is to describe the ability of critical thinking and mastery of the basic concepts of science among SMPN students in Central Lombok Regency. This type of research is a quantitative descriptive research with survey methods. Critical thinking tests and mastery of concepts by students using multiple choice instruments. The results showed that the average results: a) The critical thinking skills of nine high school students in Central Lombok were 71.69% with high criteria. The second critical thinking indicator, which provides further explanation, achieves the highest score in comparison with other indicators. b) Control of the basic concepts of natural sciences students with 76.20% with high criteria. The first indicator for controlling the concept is remembering who scores the highest score compared to other indicators